Proceedings of the International Conference on Culture and Language in Southeast Asia (ICCLAS 2017) 2018
DOI: 10.2991/icclas-17.2018.16
|View full text |Cite
|
Sign up to set email alerts
|

Translation Strategies of Islamic Terms In Indonesian-English Research Papers

Abstract: Abstract--The study examined whether strategies employed in translating Islamic terms of the research papers from Indonesian into English distorted the intended messages. Translation strategies refer to ways of transferring messages or meaning from a source language (SL) into a target language (TL). The data of the study were Islamic terms of dissertation abstracts representing different themes taken randomly from the university repository. All data were qualitatively analyzed using the concepts of translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The corpusassisted analysis of the end product of translation has shown that translators of these types of texts have employed a myriad of strategies to render the texts including formal equivalence, functional equivalence, transference, couplets, explicitations, implicitiations, and accommodations, among others. This finding of the study is in line with those of other studies that were conducted on the analysis of translation quality in different genres and languages [53][54][55][56]. It is the contention of this study, however, that the analysis of the product does not always justify the choice or the preference of one translation strategy over another.…”
Section: Discussionsupporting
confidence: 86%
“…The corpusassisted analysis of the end product of translation has shown that translators of these types of texts have employed a myriad of strategies to render the texts including formal equivalence, functional equivalence, transference, couplets, explicitations, implicitiations, and accommodations, among others. This finding of the study is in line with those of other studies that were conducted on the analysis of translation quality in different genres and languages [53][54][55][56]. It is the contention of this study, however, that the analysis of the product does not always justify the choice or the preference of one translation strategy over another.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, it can be said that this is the factor influencing the choice of calque strategy in rendering this item because the original is more highly institutionalized than its translation. In other words, the source culture foodstuff has higher cultural marked-ness than in the target culture (Farkhan, 2017).…”
Section: Direct Translationmentioning
confidence: 99%
“…As the source cultural item is completely transferred into the target culture, and its meaning does not change, this strategy is also well known as pure borrowing. It can be said substantively that both terms refer to the same concept of translation strategy (Farkhan, 2017).…”
Section: Retentionmentioning
confidence: 99%
“…The difference is that the previous research studies the equivalences in English by using translation strategies while the current research by using translation techniques. No objection with one of the findings there that the difficulties faced by translators in finding the appropriate words by translating from Quranic, Arabic or Indonesian words into English due to the different concept because of cultural background and points of view, which have to be taken into consideration [6], like for example, Muslims have two different activities, shalat as a verb and du'a as a verb, but they have only one same equivalent in English 'to pray'. This sometimes reveals a problem.…”
Section: Literature Reviewmentioning
confidence: 99%